Investing in Employees in Serbian Companies – Internal Dimension of CSR - Milena Damnjanović (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Implementation of the concept of Corporate Social Responsibility (CSR) has become important for all stakeholders and an important part of company's businesses and reporting. Little research attention is given to the research about CSR from employees' perspective and to the influence of CSR to employees. All aspects of employees' wellbeing should be a part of internal dimension of CSR. If employees perceive their company as socially responsible, they will show positive behavior towards company. This paper presents the comparative analysis of yearly reports' results from 2012 to 2017 about CSR investments in employees' wellbeing of companies which were members of Responsible Business Forum Serbia. The main goal was to determine if there was a trend in these investments. Employees have very significant role in business goals achievement but in CSR implementation also, so management should carefully define their roles in CSR implementation. The company could achieve even more benefits if it communicates effectively with employees about CSR topics. Communication channels used for CSR, such as reports and web sites, were analyzed as means to inform public, but more importantly employees about companies' CSR activities. Establishment of good relation between employees and company requires using a CSR as strategic tool.
Keywords: M14; M51; M53; M54; 330; corporate social responsibility; internal dimension; employees' wellbeing